Comparison of the Effects of Nitroglycerin, Labetalol and Lidocaine in Hypertensive Patients in Attenuation of the Endotracheal Intubation Reflex (Mugda Medical College Journal, 2024)
Background: Laryngoscopy and tracheal intubation integral parts of general anesthesia which may cause acute haemodynamic instability. Hypertensive patients are more prone of developing cardiovascular complications such as pulmonary oedema, cardiac failure and cerebrovascular haemorrhage. To attenuate such intubation reflex, some drugs are used, e.g., opioids. lidocaine sodium nitroprusside, nitroglycerin, beta blockers, calcium channel blockers etc.Objective: The purpose of the study is to see the effectiveness of nitroglycerin, labetalol and lidocaine in attenuation of intubation reflex and their anesthetic outcome in hypertensive patients.Methods: This randomized controlled study was carried out in the Department of Anesthesia, Pain, Palliative and Intensive care Medicine, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, between March and September of 2021. A total of 90 patients were included: 30 in each group as per inclusion and exclusion criteria. Group A patients received inj. nitroglycerin 2 minutes before intubation, while group B patients received inj. labetalol 0.25mg/kg 5 minutes before intubation, and group C was given 2% lidocaine 1.5mg/kg 2 minutes before intubation. Haemodynamic status of all patients was checked before and after intubation.Results: Mean age of the patients was 44.4±10.9 years in group A, 47.6±9.4 years in group B and 46.4±10.6 years in group C. Heart rate after intubation was low and statistically significant in groups-B after 1.2 and 5 minutes. Regarding mean arterial pressure (MAP), group A patients had significantly low blood pressure. Rate pressure product (RRP) of the patients was significantly low in group B at 1 minute, 2 minutes and 5 minutes. Regarding ECG changes sinus tachycardia was observed in 26.6%, 86.6% and 20% in group A, group B and group C immediately after intubation. Groups B patients showed lower incidence of sinus tachycardia than that of two other groups and showed no premature ventricular contractions, whereas group A (6.7%) and group C (3.3%) showed premature ventricular contractions.Conclusion: Labetalol showed better rhythm control, mean arterial pressure and less incidence of tachycardia. To summarize, labetalol is safer and more effective than nitroglycerin and lidocaine to attenuate the endotracheal intubation reflex in hypertensive patients.Mugda Med Coll J. 2023; 6(2): 64-70